Knowledge, Attitude and Perception Regarding the Procedure of Autopsy in COVID-19 Cases among Doctors Doing Post Mortem Examination - Anil Mangeshkar; Ashok Najan; Seema Sutay (Institute of Medico-legal Publications Pvt Ltd, 2021)
The COVID-19 pandemic has raised challenges in dealing with the dead body of deceases who have been a suspected case or a confirmed case of Covid-19, considering the extreme shortage of trained and experienced manpower in dealing with various duties and responsibilities in the COVID-19 scenario it is very important to ensure safety of the health care workers.All the guidelines issued from time to time for control of spread and treatment of Covid-19 are speculations depending on the current trends and none are based on robust research due to lack of scientific literature and work as the Covid-19 virus in new to the human race .The main driver of transmission of COVID-19is through droplets. There is unlikely to be an increased risk of COVID-19 infection from a dead body to health workers or family members who follow standard precautions while handling body. Only the lungs of dead COVID-19 patients, if handled during an autopsy, can be infectious.1and there is no evidence so far of transmission of virus through the handling of corpses.2There are a lot of speculations in the mind of forensic medicine experts regarding the ongoing mortuary work and dead body management in the Covid-19 scenario considering the risk of acquiring the infection during handing or bodies or while conducting a medico legal post mortem examination.